Comportamiento productivo en vacas lecheras holtein mestizas suplementadas con bloques nutricionales. - Satama Tene, Ángel Edmundo (2015)
In the Laboratory of Animal Nutrition and the Tunshi Experimental Station of the Faculty of Animal Sciences ESPOCH, conducted the research entitled "PRODUCTIVE BEHAVIOR Crossbred Holstein dairy cows supplemented with NUTRITIONAL BLOCKS"........................................................................